Data from a multi-year targeted proteomics study of a longitudinal birth cohort of type 1 diabetes - Lisa M. Bramer; Ernesto S. Nakayasu; Javier E. Flores; Jennifer E. Van Eyk; Michael J. MacCoss; Hemang M. Parikh; Thomas O. Metz; Bobbie-Jo M. Webb-Robertson (Scientific Data)
Abstract The deployment of liquid chromatography-mass spectrometry-based plasma proteomics experiments in a large cohort is sparse, leading to a lack of data available for benchmarking, method development or validation. Comprised of 6,426 plasma analyses, The Environmental Determinants of Diabetes in the Young (TEDDY) proteomics validation study constitutes one of the largest targeted proteomics experiments in the literature to date. The proteomics data from this study were generated over the course of 2.5 years from over 900 study subjects, each providing up to 29 longitudinal samples. The data also includes 916 quality control samples. The targeted mass spectrometry assay was comprised of 694 peptides mapping to 167 proteins and the panel was measured in each subject and QC sample. The targeted proteomic dataset presented here can be used as a resource for new computational methods development, such as for batch correction, as well as for benchmarking and comparing the performance of different methods/tools.